Prolonged noise exposure-induced auditory threshold shifts in wistar rats: Proposal of an experimental exposure protocol based on noise dose - Ana Carolina Odorizzi Zica; Gabriela Ribeiro Novanta; Maria Luiza Queiroz Sampaio; Rafael Rocha de Andrade; Lucieny Silva Martins Serra; André Luiz Lopes Sampaio (Brazilian Journal of Otorhinolaryngology)
Objective: The aim of the present study was to evaluate the effects of different doses of broadband white noise in a group of Wistar rats. Methods: The sample consisted of 6 male Wistar rats. The animals went through sequential exposures at the intensity of 95 dB for 60 min, 100 dB for 60 min and 100 dB for 120 min. Audiological evaluation was performed by Distortion Product Otoacoustic Emissions (DPOAE) exams at frequencies from 2 to 12 KHz, after each exposure/pause protocol. Statistical analysis was performed based on the values found in the DPOAE and Signal-to-Noise Ratio (S/N) in the nine exams performed over 50 days of research. Results: The study concluded that there was a compound threshold shift induced by long-term sequential noise exposure at the intensity of 100 dB for 60 min and for 120 min, with a “plateau/’ observed in the DPOAE and S/N results that coincide with the exposure period of 6 days at the intensity of 100 dB for 120 min. Conclusion: Thus, we established the proposal of an exposure protocol for research with wistar rats exposed to noise.